Assessing Mathematical Thinking Levels Of Year Six Students Using Performance Tasks - Abdullah, Nurulhidayah Lucy (2010)
This study aimed at assessing and identifying Year Six students’ mathematical thinking level using constructed response tasks. This study further explored students’ mathematical thinking levels in relation to the four mathematical thinking domains of conceptual understanding, mathematical representations, procedural fluency and mathematical explanation. It provided information whether the domains were associated and whether the different tasks used affect students’ levels of performance. The profiles of mathematical thinking involving the four mathematical thinking domains were identified for low and high achievers.